Evaluación de la resistencia a la fractura en coronas de zirconia monolítica utilizando dos tipos de agentes cementantes. (2023)
The different dental specialties use a great variety of biomaterials and dental supplies, especially in the area of oral rehabilitation, and these materials must comply with certain esthetic and of course functional characteristics. It is a matter of concern and of clinical relevance the demands of patients for fractures of crowns cemented in the mouth due to a decreased resistance to functional or parafunctional masticatory loads.